2D honeycomb transformation into dodecagonal quasicrystals driven by electrostatic forces - Sebastian Schenk; Oliver Krahn; Eric Cockayne; Holger L. Meyerheim; Marc de Boissieu; Stefan Förster; Wolf Widdra (Nature Communications, 2022)
Quasicrystals are perfectly ordered crystals lacking translational symmetry. Here the authors unravel the formation mechanism of two-dimensional dodecagonal quasicrystals that arise from systematic modifications of a hexagonal honeycomb structure.